The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1021/acsbiomaterials.1c00910
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Bath-Assisted 3D Printing for Biomedical Applications: From Pre- to Postprinting Stages

Abstract: Fluid bath-assisted three-dimensional (3D) printing is an innovative 3D printing strategy that extrudes liquid ink materials into a fluid bath to form various 3D configurations. Since the support bath can provide in situ support, extruded filaments are able to freely construct complex 3D structures. Meanwhile, the supporting function of the fluid bath decreases the dependence of the ink material's cross-linkability, thus broadening the material selections for biomedical applications. Fluid bath-assisted 3D pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 117 publications
(337 reference statements)
0
53
0
Order By: Relevance
“…The nanocomposite recovers its interactive dual microstructure faster than Pluronic F127 but slower than nanoclay with a response time of 0.36 s, which indicates that the interactions between spherical micelles and nanoclay platelets may accelerate the formation of the dual microstructure. For support bath-enabled 3D printing, a short response time is always expected , so that the support bath material can rapidly switch from liquid to solid-like states to fill the crevasse behind the nozzle translation and entrap deposited structures in situ .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The nanocomposite recovers its interactive dual microstructure faster than Pluronic F127 but slower than nanoclay with a response time of 0.36 s, which indicates that the interactions between spherical micelles and nanoclay platelets may accelerate the formation of the dual microstructure. For support bath-enabled 3D printing, a short response time is always expected , so that the support bath material can rapidly switch from liquid to solid-like states to fill the crevasse behind the nozzle translation and entrap deposited structures in situ .…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure S5a,b, the increase in nozzle diameter and dispensing pressure lead to the increase in filament diameter. In contrast, the increase in path speed, the speed at which the dispensing nozzle moves in the support bath, leads to the decrease in filament diameter, 14,19 as shown in Figure 3a. Also, when the path speed is relatively low, a swelling filament can be formed, which has a diameter larger than the nozzle diameter.…”
Section: Determination Of the Nanoclay And Pluronic F127 Concentratio...mentioning
confidence: 99%
See 1 more Smart Citation
“…In this technique, the filaments are deposited directly into a secondary shear-thinning structure that allows self-healing upon nozzle passage [123], restricting the bioink flow and allowing for the fabrication of more complex structures, with different cell types and tunable mechanical proprieties upon crosslinking (figure 4(e)) [4,124]. Recent review papers highlight the emerging solutions to embedded printing and the particular challenges in this area [125,126]. One major requirement is that the supporting bath materials do not interact/mix with the ink materials, allowing deposition with high shape and filament fidelity.…”
Section: Alternative Approaches For 3d Printingmentioning
confidence: 99%
“…In the work of Roxanne Khalaj et al [ 22 ], coronary stents were manufactured by 3D printing. Weijian Hua et al [ 23 ], showed the 3D printing method to also be a powerful tool for stent manufacturing. Kaitlyn Chua’s work also illustrates how the field of 3D printing and biomedicine can create more innovative devices and products [ 24 ].…”
Section: Introductionmentioning
confidence: 99%